2004
DOI: 10.1111/j.1365-2125.2004.02265.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of rifampicin on the expression and function of human intestinal cytochrome P450 enzymes

Abstract: AimsTo investigate the potential induction by rifampicin of intestinal CYP2C8, CYP2C9, CYP2D6 and CYP3A4 using preparations of human enterocy tes. MethodsUsing a multilumen perfusion catheter shed human enterocytes were collected from 6 healthy subjects before and after 10 days of 600 mg day -1 oral rifampicin administration. The protein expression of CYP2C8, CYP2C9, CYP2D6 and CYP3A4 as well as that of CYP3A4 mRNA was determined using Western blotting and RT-PCR, respectively. ResultsCYP3A4 mRNA expression in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(65 citation statements)
references
References 43 publications
4
60
0
1
Order By: Relevance
“…Rifampin in vivo E max optimized from intravenous data is based solely on hepatic induction, and improvement in prediction success for oral DDIs can be expected only if induction effect is the same in intestine and liver. Data on rifampin induction of CYP3A4 mRNA and protein in enterocytes are limited and based on a small group of healthy subjects, with no corresponding matched hepatic induction data (Glaeser et al, 2005). However, this study indicated differential and lower intestinal response to rifampin relative to liver.…”
Section: Downloaded Frommentioning
confidence: 85%
“…Rifampin in vivo E max optimized from intravenous data is based solely on hepatic induction, and improvement in prediction success for oral DDIs can be expected only if induction effect is the same in intestine and liver. Data on rifampin induction of CYP3A4 mRNA and protein in enterocytes are limited and based on a small group of healthy subjects, with no corresponding matched hepatic induction data (Glaeser et al, 2005). However, this study indicated differential and lower intestinal response to rifampin relative to liver.…”
Section: Downloaded Frommentioning
confidence: 85%
“…Nevertheless, we postulate that CYP2C8 induction only has a minimal effect on repaglinide pharmacokinetics, because (i) repaglinide systemic clearance is majorly determined by the hepatic uptake clearance and an increase in hepatic metabolic activity is less likely to affect the systemic clearance (Table 2), and (ii) as noted with the simulations here, increase in the gut metabolism is the major driver for observed decrease in repaglinide exposure (particularly when rifampicin and repaglinide doses were separated by .12 hours), and CYP2C8 contribution to the gut metabolism is believed to be relatively low (Paine et al, 2006). Nevertheless, although no clinical evidence exist, expression and in vitro data suggest that rifampicin significantly induces the intestinal CYP2C8 and CYP2C9 isoforms and may partially contribute to such interactions (Lapple et al, 2003;Glaeser et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Hepatic CYP3A4 is induced by rifampicin and is regulated mainly by PXR (Drocourt et al, 2002). Intestinal CYP3A4 is induced by 1a,25-dihydroxyvitamin D 3 through vitamin D receptor and is also induced by rifampicin (Kolars et al, 1992;Glaeser et al, 2005;van de Kerkhof et al, 2008). In our differentiated enterocytes, not only CYP3A4 mRNA expression but also CYP3A4/5 activity were induced by 1a,25-dihydroxyvitamin D 3 (Fig.…”
Section: Differentiation Of Human Ips Cells To Enterocytes 607mentioning
confidence: 95%